2020
DOI: 10.1111/jan.14690
|View full text |Cite
|
Sign up to set email alerts
|

Development of nurse practitioner metaspecialty clinical practice standards: A national sequential mixed methods study

Abstract: Aim To achieve profession‐wide consensus on clinical practice standards for six broad Australian nurse practitioner specialty areas (termed metaspecialties). Design Sequential mixed methods with initial interpretive study (Interpretive Phase) followed by modified three‐round Delphi study (Survey Phase). Methods Participants from all Australian jurisdictions were recruited. Main eligibility criterion was current endorsement as a nurse practitioner for 12 or more months. Interpretive Phase comprised in‐depth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…More recently, it has been suggested that implementing standardised education streams aligned with national health priorities (including primary health) and replacing the significant advanced practice experience hours with competency-based assessments [ 37 ]. Another recent Australian study sought industry consensus on key skills and competencies for various NP meta-specialities, including primary care, to help guide local and international NP education [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it has been suggested that implementing standardised education streams aligned with national health priorities (including primary health) and replacing the significant advanced practice experience hours with competency-based assessments [ 37 ]. Another recent Australian study sought industry consensus on key skills and competencies for various NP meta-specialities, including primary care, to help guide local and international NP education [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…This lack of standardization can lead to confusion and inconsistencies in the recognition and utilization of APNs. Title protection for APNs is essential to ensuring the quality and safety of healthcare services and enabling role regulation (Gardner et al., 2021; Wheeler et al., 2022). International collaborations and partnerships can help address these issues by providing opportunities for exchanging knowledge, expertise, and experience, promoting cultural competence and standardization, and advancing nursing education and practice.…”
Section: Evidence/literature Reviewmentioning
confidence: 99%
“…While A. Gardner et al (2021) identified that specific standards for practice for NNP have been articulated, and recently updated (see Bonner et al, 2021), little is known about the practice profile and patterns of NNP in Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…G. Gardner et al (2016), in a national survey of Australian nurses also using the modified Strong Model of Advanced Practice, found that NP have different practice patterns to those of registered nurses, clinical nurse specialists, clinical nurse consultants and nurse educators. While A. Gardner et al (2021) identified that specific standards for practice for NNP have been articulated, and recently updated (see Bonner et al, 2021), little is known about the practice profile and patterns of NNP in Australia.…”
Section: Literature Reviewmentioning
confidence: 99%